Effect of Nutrient Concentration AB Mix and Liquid Organic Fertilizer of Broiler Chicken Eggsshell Against Growth and Yieldmustard Plant Caisim (Brassica juncea L. Czern. Var. Tosakan) Hydroponically - K. Kartika Pratiwi; I Gusti Made Arjana; I Nengah Suaria (Warmadewa University Press, 2023)
Along with the increasing population, people's needs for highly nutritious foods, such as vegetables, are increasing [14] but the available agricultural land, especially in urban areas, is increasingly limited. Vegetable crops that have enough economic value besides cabbage crop, cabbage flowers and broccoli are mustard caisim plants. Mustard caisim plants contain many benefits, the content contained in mustard caisim is protein, fat, carbohydrates, Ca, P, Fe, Vitamin K, Vitamin A, Vitamin 10 B, and Vitamin C. Hydroponic farming systems are one alternative that can answer these problems. The purpose of this study was to determine the effect of nutrient concentration of AB MIX and liquid organic fertilizer broiler chicken eggshells on the growth and yield of mustard caisim plants (Brassica juncea L. Czern. Var. Tosakan) hydroponically. The study method was prepared using Mirosoft Excel 2010 followed by a 5% BNT Test, consisting of five treatments and four repeats so that 20 samples were obtained. Treatment K1 = Nutrition AB-Mix, K2 = AB-Mix + 10cc liquid organic fertilizer, K3 = AB-Mix + 20cc liquid organic fertilizer, K4 = AB-Mix + 30cc, liquid organic fertilizer K5 = AB-Mix + 40cc liquid organic fertilizer. The results showed that the highest economic result weight was obtained from the treatment of ABMix + 10cc liquid organic fertilizer (K2) nutrient concentration which was 73.3 g or an increase of 46.50% when compared to the lowest economic result weight at AB-Mix + 40cc liquid organic fertilizer (K5) nutrient concentration which was only 44.8 g.